Fiber‐optic detector for real time dosimetry of a micro‐planar x‐ray beam. Issue 4 (27th March 2015) - Belley, Matthew D.; Stanton, Ian N.; Hadsell, Mike; Ger, Rachel; Langloss, Brian W.; Lu, Jianping; Zhou, Otto; Chang, Sha X.; Therien, Michael J.; Yoshizumi, Terry T.
Abstract : Purpose: Here, the authors describe a dosimetry measurement technique for microbeam radiation therapy using a nanoparticle‐terminated fiber‐optic dosimeter (nano‐FOD). Methods: The nano‐FOD was placed in the center of a 2 cm diameter mouse phantom to measure the deep tissue dose and lateral beam profile of a planar x‐ray microbeam. Results: The continuous dose rate at the x‐ray microbeam peak measured with the nano‐FOD was 1.91 ± 0.06 cGy s −1, a value 2.7% higher than that determined via radiochromic film measurements (1.86 ± 0.15 cGy s −1 ). The nano‐FOD‐determined lateral beam full‐width half max value of 420 μm exceeded that measured using radiochromic film (320 μm). Due to the 8° angle of the collimated microbeam and resulting volumetric effects within the scintillator, the profile measurements reported here are estimated to achieve a resolution of ∼0.1 mm; however, for a beam angle of 0°, the theoretical resolution would approach the thickness of the scintillator (∼0.01 mm). Conclusions: This work provides proof‐of‐concept data and demonstrates that the novel nano‐FOD device can be used to perform real‐time dosimetry in microbeam radiation therapy to measure the continuous dose rate at the x‐ray microbeam peak as well as the lateral beam shape.